2010
DOI: 10.1089/ten.tec.2009.0327
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Ciliated Cells from Avian Embryonic Stem Cells Using Three-Dimensional Matrix

Abstract: We have devised a simple three-dimensional (3D) tissue-culturing method to induce ciliogenesis from avian embryonic stem (ES) cells by using avian fertilized eggs. Unlike the previous reported techniques, this method does not require trypsinization, which would reduce the viability of the cells; it also does not require an airliquid interface to induce ciliogenesis and to maintain the growth of the induced ciliated cells. ES cells seeded and attached on this collagen-coated chitosan 3D gel grew spontaneously a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…9,10 Recent studies have also demonstrated that matrix protein composition, 3D scaffolds, and mechanical forces can influence differentiation of embryonic stem cells (ESCs) to lung epithelium. 17,[29][30][31][32] As such, use of different artificial 3D scaffolds is a powerful technique for generating functional lung tissue ex vivo.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Recent studies have also demonstrated that matrix protein composition, 3D scaffolds, and mechanical forces can influence differentiation of embryonic stem cells (ESCs) to lung epithelium. 17,[29][30][31][32] As such, use of different artificial 3D scaffolds is a powerful technique for generating functional lung tissue ex vivo.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the amount of continuous pressure of the media delivered through the vasculature to the re-epithelialized scaffold influenced cell survival, with 20 cm H 2 O being optimal. The fact that the CF and MP protocols were unable to sustain cell viability was a surprising finding, as other investigators have published on cell viability using de-cellularized scaffolds generated by the MP method with A549 cells, fetal pulmonary cells, murine embryonic stem cells, or mesenchymal stem cells [10,16,1820,23,24,26,27]. Furthermore, other investigators have utilized the MP de-cellularization approach and have been able to support C10 cells for 1 month [18].…”
Section: Discussionmentioning
confidence: 99%
“…93 However, recent studies have shown that the use of embryonic stem cells can be used to bypass the air-liquid culture step. 94 Nevertheless, this approach requires longer culture periods and does not represent the overall diversity of the cells in the airway epithelium. The cell phenotype can also be affected by changing the substrate to hyaluronan or collagen type IV.…”
Section: Epithelium In Clinical Full Organ/multicellular Tissue-enginmentioning
confidence: 99%